PENGARUH EFIKASI DIRI TERHADAP KINERJA KARYAWAN MELALUI INOVASI SEBAGAI VARIABEL INTERVENING (STUDI PADA DIVISI SEKRETARIAT DAN HUMAS PDAM SURYA SEMBADA KOTA SURABAYA) - EKA DESIANA, NOFI (Jurnal Ilmu Manajemen (JIM), 2018)
PDAM Surya Sembada Surabaya City hopes to be as successful as expected, it looks good and behaves well enough, and the condition of self-confidence is also quite good. In addition, the innovations carried out are also good enough, and employee performance is also optimal. This study aims to analysis of the effect of self-efficacy on employee performance, to determine the test results and analysis of the effect of self-efficacy on innovation, to determine the results of the test and analysis of the effect of innovation on employee performance, and analyze the effect of self-efficacy on employee performance through innovation as an intervening variable. This research is a causal research that uses a quantitative approach. The sampling technique uses 52 saturated samples and the whole questionnaire returns. Statistical analysis is Structural Equation Modeling (SEM) with the help of SmartPLS software. The results of the study prove that self-efficacy has a significant positive effect on employee performance. Self-efficacy has a significant positive effect on innovation. Innovation has a significant positive effect on employee performance. Innovation acts as a mediation of the interaction of the effect of self-efficacy on employee performance. Keywords: employee performance; innovation; self-efficacy.